2018
DOI: 10.1016/j.tibtech.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Protein- and Peptide-Based Biosensors in Artificial Olfaction

Abstract: Animals' olfactory systems rely on proteins, olfactory receptors (ORs) and odorant-binding proteins (OBPs), as their native sensing units to detect odours. Recent advances demonstrate that these proteins can also be employed as molecular recognition units in gas-phase biosensors. In addition, the interactions between odorant molecules and ORs or OBPs are a source of inspiration for designing peptides with tunable odorant selectivity. We review recent progress in gas biosensors employing biological units (ORs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 82 publications
0
93
0
Order By: Relevance
“…Full-size  DOI: 10.7717/peerj.8902/ fig-8 insect population management, as well as other biotechnological applications (Brito, Moreira & Melo, 2016). It was recently demonstrated that OBPs can function as molecular recognition units in gas-phase biosensors (Barbosa, Oliveira & Roque, 2018) including OBP22 of Aedes aegypti (Zhao et al, 2012). We identified 16 putative OBPs including 2 GOBPs and 3 PBPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-size  DOI: 10.7717/peerj.8902/ fig-8 insect population management, as well as other biotechnological applications (Brito, Moreira & Melo, 2016). It was recently demonstrated that OBPs can function as molecular recognition units in gas-phase biosensors (Barbosa, Oliveira & Roque, 2018) including OBP22 of Aedes aegypti (Zhao et al, 2012). We identified 16 putative OBPs including 2 GOBPs and 3 PBPs.…”
Section: Discussionmentioning
confidence: 99%
“…ORs combine olfactory sensory neurons with binding proteins and they function in olfactory signal transduction, which also uses native sensing units to detect odors. In addition, the interactions between odorant molecules and ORs or OBPs are a source of inspiration for the design of peptides with tunable odorant selectivity (Barbosa, Oliveira & Roque, 2018;Venthur & Zhou, 2018). Insect olfactory receptors are dimers consisting of constant and variable regions (Horsfield, Haase & Turin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Insect OBPs, which exhibit superior stability, are assumed to have a broad molecular receptive range [42] and genetic modification has been suggested to improve their binding affinities [43]. Further description of OBPs biotechnology applications and specifically biosensing can be found in the literature [44,45]. Table 1.…”
Section: Or-based Bioelectronic Nosementioning
confidence: 99%
“…Here, we focus on the main strategies that can be adopted to reach this goal ( Figure 2). More detailed reviews are available that list the sensors developed so far with this approach [8,12,13].…”
Section: Design Of Biomimetic Sensing Materialsmentioning
confidence: 99%